Analysis and evaluation of differential inductive transducers for transforming physical parameters into usable output frequency signal - A., Deji; S., Khan; M. M., Ahmed; J., Chebil; A. H. M. Z., Alam (academicjournals, 2014)
This paper presents a novel hybrid oscillating inductive sensor circuit converting deflection oscillations into useful signal and thus being used to support an oscillatory circuit mechanism and management of their resulting oscillation in a real-time implementation. This circuit does not only detects and optimizes the deflections produced in an oscillation in instrumentation electronics, but also provide an improved sensory with high accuracy, sensitivity, responsiveness and operating range. The design therefore help in transforming the deflection deviations in the in and out movement of the core into useful output content. A simulation and derivation of the oscillating circuit in see-saw convulsion bar sensing system has been implemented. Simulation and derivations shows how the oscillating circuits of the bar are converted into frequency, duty cycle, current, voltages for further wireless applications.